1998
DOI: 10.1093/fampra/15.2.119
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of a new treatment for somatized mental disorder taught to GPs

Abstract: Training GPs with the reattribution training package appears to be extremely cost-effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
92
1
5

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(100 citation statements)
references
References 0 publications
2
92
1
5
Order By: Relevance
“…Studies of reattribution interventions, although not in patients with cancer and chronic pain, have found short-term psychological improvements (Morriss, et al, 1999). Interventions aiming to make HNC patients internalise the BPS framework to manage pain should be evaluated in future research.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of reattribution interventions, although not in patients with cancer and chronic pain, have found short-term psychological improvements (Morriss, et al, 1999). Interventions aiming to make HNC patients internalise the BPS framework to manage pain should be evaluated in future research.…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely adopted internationally. [7][8][9][10][11][12][13][14] Features of reattribution are that: psychological context can help explain physical symptoms; attributions for symptoms held by patients are unhelpful; broadening patients' attributions will resolve/improve symptoms or enable GPs to treat any underlying psychological or social problems.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14] A recent UK primary care trial (MUST) demonstrated that GPs can be taught by non-expert trainers to deliver reattribution within routine consultations. 5 GPs' communication changed significantly; trained physicians elicited more patient concerns/beliefs and provided richer symptom explanations that linked physical symptoms to psychosocial issues.…”
Section: Introductionmentioning
confidence: 99%
“…This programme was taught in brief courses (eight hours in total) and adopted a cognitive-oriented approach. The model has been tested in the UK in before-and-after studies and in the Netherlands in a randomized controlled trial demonstrating that GPs acquired the necessary interviewing skills [25], a reduction in overall health care cost [26], a change in patients' health beliefs [27] and an improvement in patients' health [28,29].…”
Section: Treatment Of Somatizationmentioning
confidence: 99%